ANALISIS PENGARUH SHOCKPADA INDEKS HARGA SAHAM GABUNGAN SEKTORAL BEJ (JASICA) TERHADAP SEKTOR LAINNYA (APLIKASI MODEL VECTOR AUTOREGRESSIVE) - Dewi, Katri Septiana; Arfinto, Erman Denny (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2007)
This research examines wether there is a causal relationship among ten sectoral indexes in Jakarta Stock Exchange (JASICA). Ten sectoral indexes are examined to determine their relationships and how shock to one index are transmitted to the others. The Vector Autoregressive (VAR) method is applied to analyze daily time series data from January 3rd, 2002 to December 28th, 2006. Our findings provide important information about the transmision of shock among these indexes. First, there are r.ausal relationships among indexes. Second, sectoral i;;dex quickly responses to the shocks in the other indexes.